Richness of Wild Bees (Hymenoptera: Apidae) in a Forest Remnant in a Transition Region of Eastern Amazonia - Luciano André Chaves Ferreira; Denilson Costa Martins; Márcia Maria Corrêa Rêgo; Patrícia Maia Correia de Albuquerque (Psyche: A Journal of Entomology)
Eastern Amazonia is an area with great biological diversity that has suffered rapid deforestation and forest fragmentation over the years. Because of the scarcity of data on the fauna and flora, the northwest of the state of Maranhão has become a priority area for studies that seek to gain a better understanding of bee fauna. Between August 2013 and December 2014, in collections at two-month intervals, a total of 1047 bees belonging to 70 species were collected using two methods (an insect net and scent-baited traps). Apinae was the most abundant subfamily and had the greatest species richness (63 species and 1039 individuals); the most notable tribes in this subfamily were Meliponini (20 species and 445 individuals) and Euglossini (24 species and 452 individuals). In all, 62.8% of the total richness was sampled with an insect net and 34.2% with bait traps. Bees were present in every collection month, and August and December were the months with the greatest richness and abundance, respectively. Although the species accumulation curve did not stabilize, the results were positive as three new species were recorded for the Maranhão state: Bombus transversalis (Olivier, 1789); Xylocopa suspecta Moure and Camargo, 1988; and Xylocopa macrops Lepeletier, 1841, and eleven for the Amazonian region of the state.